Kinerja Badan Pemadam Kebakaran Dalam Menanggulangi Kebakaran Di Kabupaten Rokan Hilir - DARMADI, DIDIT; ", SUJIANTO (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
DIDIT DARMADI. Performance Unit Fire Company In Overcoming Fire in Sub-Province of Rokan Hulu guiding by Prof. Dr. H. Sujianto, This research take regional place of Sub-Province of Rokan Hilir, as for problem of this research is formulated in formulation of problem that is as which Performance Unit Fire Company In Overcoming Fire in Sub-Province of Rokan Hulu. And then, factorsn of any kind of influencing Performance Unit Fire Company in Overcoming fire in Sub-Province of Rokan Hilir. This research use descriptive method by using theory which in telling by some writer concerning Organizational Performance. In this research of researcher use indicator namely job efficiency, team cooperation, and head relation with subordinate as Performance Unit Fire Company In Overcoming Fire in Sub-Province of Rokan Hilir. Research method the used is method research of field with data collecting technique, interview and field obserfasi with specified research informan pursuant to technique of purposive sampling. As primary data is the source of information in which can through interview with data and informan of sekunder obtained to through relevant books and document with this topic of research. From result of descriptive analysis qualitative that Performance Unit Fire Company in Overcoming Fire in Sub-Province of Rokan Hilir categorized not yet good and still a lot have to in improve, and repairing. In this research is known by factors influencing Performance Unit Fire Company in Overcoming Fire in Sub-Province of Rokan hilir for example facilities and basic facilities factor which still very less, and then, less adequate human resource factor and factor of Financial ( Money). Therefore, utilize to support performance walk better at fire company needed by addition at resource of manusi, more adequate equipments in its operational and also conduct socialization tosociety utilize to grow awareness and knowledge of danger of fire. And also conductanalysis or sighting to existence of fire company in perumpunan of business placedby Kesbangpolin and fire company.Keyword : Performance, cervicing, capability, Performance Fire Company.